DISKURSUS PROYEK ISLAMISASI ILMU PENGETAHUAN ISMAIL RAJI AL-FARUQI - Nurhayati, Nurhayati; Mustamin, Kamaruddin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
The Scientific Integration Project is a major issue at the University, especially in Indonesia. The style and form of integration carried out vary according to the vision and mission of each tertiary institution. A number of studies have discussed the integration project, but not many have touched on the basis and philosophy behind the project. This article aims to examine the embryo of scientific integration by exploring the Islamization project of Ismail Raji Al-Faruqi’s science. This research is purely a literature study by collecting data from books and articles both written by Ismail Al-Faruqi and others. The results showed that despite receiving responses and pros and cons for Muslim scholars about the project, the project has made a major contribution to the development of scientific integration in a number of countries. The integration is then carried out differently according to the vision and mission of a tertiary institution